THE EFFECT OF PODCASTING TECHNOLOGY MEDIA ON STUDENTS’ LISTENING SKILL IN MADRASAH ALIYAH SWASTA AL-WASHLIYAH GEDUNG JOHOR - Prasisca, Dhea; Harahap, Yulia Sari; Zulfitri (JURNAL ILMU PENDIDIKAN, 2024)
This study investigated the effect of podcasting technology media on students’ listening skill in madrasah al-washliyah swasta gedung johor. This study used quantitative research method. The researcher selected 86 students in Madrasah Aliyah Swasta Al-Washliyah Gedung Johor in the school year 2024/2025 from the total number, 43 students from X B and 43 students from class X C to become a sample in this research. This research employed a test (pre-test and post-test) as an instrument and also observation and documentation as a compliment. A listening test used as the research instrument. To analyzed data, the researcher used SPSS. there is significant affect of using podcast technology media for students, especially in English listening skill. students who taught by using podcast technology media got higher score than students who taught without using podcast technology media. It can be seen the mean score of experimental class was 87 while the mean score of control group was 76. podcasts have a greater impact on students listening skill than traditional classroom settings. Additionally, it was shown that teaching listening through podcast media may be enhanced because learning Englis hmade the students more engaging, joyful, and enjoyable. In conclusion, podcasts can have a major impact on kids' listening comprehension at the tenth grade level.